ITIL® 4 Foundation Revision Guide - LIMITED, AXELOS (The Stationery Office Ltd, 2019)
ITIL® 4 has evolved from the previous, ITIL v3, version by re-shaping much of the established ITSM practices in the wider context of customer experience, value streams and digital transformation, as well as embracing new ways of working such as Lean, Agile, and DevOps.